Effects of a high-intensity intermittent training program on aerobic capacity and lipid profile in trained subjects - Ouerghi N; Khammassi M; Boukorraa S; Feki M; Kaabachi N; Bouassida A (Dove Medical Press, 2014)
Nejmeddine Ouerghi,1,2 Marwa Khammassi,1 Sami Boukorraa,1 Moncef Feki,2 Naziha Kaabachi,2 Anissa Bouassida,1,3 1Research Unit, Sportive Performance and Physical Rehabilitation, High Institute of Sports and Physical Education of Kef, University of Jendouba, Kef, Tunisia, 2Laboratory of Biochemistry, Rabta Hospital, Faculty of Medicine of Tunis, El Manar University, Tunis, 3Physiology Laboratory, Faculty of Medicine Ibn el Jazzar, Sousse, Tunisia Background: Data regarding the effect of training on plasma lipids are controversial. Most studies have addressed continuous or long intermittent training programs. The present study evaluated the effect of short-short high-intensity intermittent training (HIIT) on aerobic capacity and plasma lipids in soccer players. Methods: The study included 24 male subjects aged 21–26 years, divided into three groups: experimental group 1 (EG1, n=8) comprising soccer players who exercised in addition to regular short-short HIIT twice a week for 12 weeks; experimental group 2 (EG2, n=8) comprising soccer players who exercised in a regular football training program; and a control group (CG, n=8) comprising untrained subjects who did not practice regular physical activity. Maximal aerobic velocity and maximal oxygen uptake along with plasma lipids were measured before and after 6 weeks and 12 weeks of the respective training program. Results: Compared with basal values, maximal oxygen uptake had significantly increased in EG1 (from 53.3±4.0 mL/min/kg to 54.8±3.0 mL/min/kg at 6 weeks [P<0.05] and to 57.0±3.2 mL/min/kg at 12 weeks [P<0.001]). Maximal oxygen uptake was increased only after 12 weeks in EG2 (from 52.8±2.7 mL/min/kg to 54.2±2.6 mL/min/kg, [P<0.05]), but remain unchanged in CG. After 12 weeks of training, maximal oxygen uptake was significantly higher in EG1 than in EG2 (P<0.05). During training, no significant changes in plasma lipids occurred. However, after 12 weeks, total and low-density lipoprotein cholesterol levels had decreased (by about 2%) in EG1 but ...